Patient‐individualized CD8+ cytolytic T‐cell therapy effectively combats minimal residual leukemia in immunodeficient mice. Issue 5 (5th October 2015) - Distler, Eva; Albrecht, Jana; Brunk, Ariane; Khan, Shamsul; Schnürer, Elke; Frey, Michaela; Mottok, Anja; Jordán‐Garrote, Ana‐Laura; Brede, Christian; Beilhack, Andreas; Mades, Andreas; Tomsitz, Dirk; et al.
Abstract : Adoptive transfer of donor‐derived cytolytic T‐lymphocytes (CTL) has evolved as a promising strategy to improve graft‐versus‐leukemia (GvL) effects in allogeneic hematopoietic stem‐cell transplantation. However, durable clinical responses are often hampered by limited capability of transferred T cells to establish effective and sustained antitumor immunity in vivo . We therefore analyzed GvL responses of acute myeloid leukemia (AML)‐reactive CD8 + CTL with central and effector memory phenotype in a new allogeneic donor‐patient specific humanized mouse model. CTL lines and clones obtained upon stimulation of naive CD45RA + donor CD8 + T cells with either single HLA antigen‐mismatched or HLA‐matched primary AML blasts, respectively, elicited strong leukemia reactivity during cytokine‐optimized short to intermediate ( i.e ., 2–8 weeks) culture periods. Single doses of CTL were intravenously infused into NOD/scidIL2Rcg null mice when engraftment with patient AML reached bone marrow infiltration of 1–5%, clinically defining minimal residual disease status. This treatment resulted in complete regression of HLA‐mismatched and strong reduction of HLA‐matched AML infiltration, respectively. Most importantly, mice receiving AML‐reactive CTL showed significantly prolonged survival. Transferred CTL were detectable in murine bone marrow and spleen and demonstrated sustained AML‐reactivity ex vivo . Moreover, injections with human IL‐15 clearly promoted CTL persistence. In summary, we show that naive donor‐derived CD8 + CTL effectively combat patient AML blasts in immunodeficient mice. The donor‐patient specific humanized mouse model appears suitable to evaluate therapeutic efficacy of AML‐reactive CTL before adoptive transfer into patients. It may further help to identify powerful leukemia rejection antigens and T‐cell receptors for redirecting immunity to leukemias even in a patient‐individualized manner. Abstract : What's new? Adoptive transfer of donor‐derived cytolytic T‐lymphocytes (CTL) is a promising strategy for improving graft‐versus‐leukemia (GvL) effects in allogeneic hematopoietic stem‐cell transplantation. Transferred T cells however show limited capability to establish effective and sustained antitumor immunity in vivo . Here, the authors develop a humanized mouse model for evaluating the GvL effect of acute myeloid leukemia‐reactive CTL generated in vitro from naive CD45RA + CD8 + T cells of healthy donors. CTL production uses clinical samples from donor‐patient pairs with either full HLA match or one‐antigen mismatch. Single CTL infusion into mice with minimal residual disease mediates significant leukemia regression and prolonged survival of animals.